1999 Footwear Symposium in Canmore / Canada (August 5-7, 1999)
Manuskripte zur Schuh-Sysmpsium 1999 in Canmore/Kanada Dr. Joseph Hamill - Evaluation of Shock Attenuation. Dr. Thomas Milani - Perception - The Relationship of Biomechanical and Subjective Data Special Seminar: Biomechanically Driven Developments in Sport Shoe Technology Dr. Simon Luethi - Adidas Feet You Wear Technology Dr. Martyn Shorten - Nike Tuned Air Technology Dr. Yasunori Kaneko - Mizuno Wave Plate Technology Symposium Manuscripts E. Avramakis, A. Stacoff, E. Stüssi - Shoe design and lateral stability in floorball G. Baroud , U.-J. Goerke , H. Guenther, D.J. Stefanyshyn, J.E. Miller, B.M. Nigg - A non-linear hyperplastic finite element model of energy return enhancement in sport surfaces and shoes O. Bloch, W. Potthast and G.-P. Brüggemann - Pressure distribution during sliding on tennis clay court D. Borges Machado and E. M. Hennig - The influence of daily activity movement patterns on the in-shoe plantar pressure distribution of children S.J. Dixon and D.G. Kerwin - Heel lift influence on Achilles tendon loading S. Grau, F. Mayer, I. Krauß, M. Beck, W. Bäurle, H. Baur, Ch. Maiwald - Biomechanical analysis of the chronis Achillodynia in runners MJ. Kurz, and N. Stergiou - The influence of footwear and shoe hardness on lower extremity intralimb voordination strategies M.A. Nurse, B.M. Nigg, S. Deazeley - Effects of forefoot orthotic posting on the kinematics of the lower extremities during walking David J. Pearsall, René A. Turcotte, David L. Montgomery - Assessing ice hockey skate boots stiffness T. F. Sterzing, E. M. Hennig - Measurement of plantar pressures, rearfoot motion and tibila shock during running 10 km on a 400 m track R.E. Wunderlich and P.R. Cavanagh - Sexual dimorphism in foot shape E. B. Barry, P. D. Milburn - A footwear traction measuring device E. B. Barry, P. D. Milburn - A mechanism explaining traction on footwear on natural surfaces N. Benjuya - THE EFFECTIVENESS OF HEEL-BASED REPLACEMENT INSOLES ON THE KINETICS AND KINEMATICS OF LOCOMOTION U.G. Kersting, H. Böhm., G.-P. Brüggemann - INTERNAL LOADING OF THE LOWER EXTREMITY DURING RUNNING OBTAINED BY TWO DIFFERENT CALCULATION METHODS V.R. Coyles and M.J.Lake - FOREFOOT PLANTAR PRESSURE DISTRIBUTION INSIDE THE SOCCER BOOT DURING RUNNING D.De Clercq, B.De Wit - TIMING OF LOWER EXTREMITY MOTIONS DURING BAREFOOT AND SHOD RUNNING AT THREE DIFFERENT VELOCITIES B. Dychko - METHOD OF EVALUATION OF POWERABSORPTION PROPERTIES OF A BIOMECHANICAL SYSTEM " LOCOMOTORIUM - SPORTS FOOTWEAR - ARTIFICIAL COVER ". K. Ford MS, J. Stern DPM, C. Morin - DPM IN-SKATE PRESSURE DISTRIBUTION DIFFERENCES WITH A CUSTOM MOLDED ORTHOTIC James G. Foto, James A. Birke - USING BENCH TOP METHODS TO EVALUATE DUAL-DENSITY MATERIALS USED IN THERAPEUTIC FOOTWEAR P.Freychat and N. Bouche - DYNAMIC ARCH DEFORMATION AND ITS CONSEQUENCE ON SHOE DESIGN A.C. García, A. Martínez, J.S. Solaz, J. Montero, J.V. Durá, J.F. Ramiro - DEVELOPMENT OF A METHOD FOR MEASURING HORIZONTAL FORCES IN SOCCER BOOTS STUDS DURING SKILLS PERFOMANCE B. Van Gheluwe and B. Nelen - PLANTAR FOOT PRESSURE OF LOWER LEG AMPUTEES DURING GAIT AND RUNNING J.C. Gonzalez, A. C. García, M. J. Vivas, E. Ferrús, E. Alcántara, A. Forner - A NEW PORTABLE METHOD FOR THE MEASUREMENT OF PRESSURE-DISCOMFORT THRESHOLD (PDT) ON THE FOOT PLANT E. M. Hennig, O. Zulbeck - THE INFLUENCE OF SOCCER BOOT CONSTRUCTION ON BALL VELOCITY AND SHOCK TO THE BODY Alan Hreljac, & Robert N. Marshall - THE EFFECT OF VARYING MIDSOLE HARDNESS ON FORCE ATTENUATION AND REARFOOT MOVEMENT DURING RUNNING: A META-ANALYSIS U.G. Kersting, J. Neumann - THE EFFECT OF CONTROLLED VARIATIONS IN RUNNING STYLE ON REARFOOT MOVEMENT AND GROUND REACTION FORCES M. Kouchi, M. Mochimaru - DO SIMILARITIES IN FOOT SURFACE FORMS REFLECT SIMILARITIES IN FOOT BONE STRUCTURE? D. Lafontaine and M. Lamontagne - TIMING AND VALUES OF PEAKS OF PLANTAR PRESSURE AND FORCE FOR ALPINE SKI INSTRUCTORS PERFORMING A VARIETY OF TURNS ON GROOMED TERRAIN M. J. Lake and B. L. Patritti - SIGNAL PROCESSING APPROACHES TO EVALUATE THE PERFORMANCE OF SHOCK ABSORBING INSERTS FOR FOOTWEAR B. L. Patritti and M. J. Lake - IN VIVO ASSESSMENT OF THE SHOCK ABSORPTION CHARACTERISTICS OF ATHLETIC FOOTWEAR INSERT MATERIALS L.B. Rosenfeld, J.Ronsky, P. Wiley, D. Caswell - ARE THE KINETIC AND KINEMATIC CHANGES TO GAIT CAUSED BY FOOT ORTHOTIC USE IN A PRONATED POPULATION PERMANENT, OR MITIGATED DURING A ONE-MONTH PERIOD OF ADAPTATION Martyn Shorten, Bin Xia, Tim Eng and Dan Johnson - IN-SHOE PRESSURE DISTRIBUTION: AN ALTERNATIVE APPROACH TO ANALYSIS D.J. Stefanyshyn, P. Stergiou, V.M.Y. Lun, W.H. Meeuwisse, B.M. Nigg - KNEE JOINT MOMENTS AND PATELLOFEMORAL PAIN SYNDROME IN RUNNERS PART I: A CASE CONTROL STUDY; PART II: A PROSPECTIVE COHORD STUDY Sadayuki Ujihashi, Mitsuhiro Iwasaki, Katsumasa Tanaka and Norio Inou - CORRELATIONS BETWEEN THE MECHANICAL PROPERTIES OF RUNNING SHOES/ ARTIFICIAL TRACKS AND THE SENSORY EVALUATIONS BY DISTANCE RUNNERS